Untreated wheat straw: Potential source for diverse cellulolytic enzyme secretion by Penicillium janthinellum EMS-UV-8 mutant. (November 2015) - Sharma, Bhawna; Agrawal, Ruchi; Singhania, Reeta Rani; Satlewal, Alok; Mathur, Anshu; Tuli, Deepak; Adsul, Mukund
Graphical abstract: Highlights: Wheat straw (WS) was pretreated to get variability in chemical composition. Cellulolytic enzymes were produced by using chemically and structurally different WS. Amorphous pretreated wheat straw/cellulose gave higher cellulase production. Enzyme produced by using untreated WS gave better pretreated wheat straw hydrolysis. Untreated wheat straw is a good carbon source for diverse cellulase secretion. Abstract: Study describes the production of cellulases by Penicillium janthinellum EMS-UV-8 using untreated wheat straw (WS), treated WS (acid, alkali, steam exploded, organo-solv) and pure cellulosic substrates (avicel, cellulose-II and carboxymethyl cellulose). Severely pretreated WS and cellulose-II produced more cellulolytic enzymes than untreated samples. XRD and FTIR analysis revels that the increase in the amorphous structure of pretreated WS/cellulose increases enzyme production. Enzyme samples prepared using different substrates were used for the hydrolysis of dilute acid treated wheat straw (DATWS), steam exploded wheat straw (SEWS) and avicel. The enzyme prepared using untreated WS gave more hydrolysis of DATWS and SEWS than the enzyme prepared using pretreated WS or pure cellulosic substrates. This revels that more diverse/potential enzymes were secreted by P. janthinellum EMS-UV-8 mutant using untreated WS. This study may contribute in production of efficient enzyme mixture/cocktail by single fungal strain for economic conversion of biomass to sugars.